Value of preoperative computed tomography in predicting the local staging of cancer of the tongue at primary surgery. Issue 8 (October 2020) - Fu, J.-Y.; Zhu, L.; Li, J.; Chen, P.-Q.; Zhang, C.-Y.; Shi, W.-T.; Shen, S.-K.; Zhang, C.-P.; Zhang, Z.-Y.
Abstract: Preoperative staging is essential for the planning of treatment of cancer. This study was designed to evaluate the accuracy of computed tomography (CT) in predicting the local stage of tongue cancer by comparing it with the gold standard of histopathology. A total of 233 patients with newly-diagnosed tongue cancer was retrospectively reviewed, and the size of the tumour and the status of the cervical lymph node were compared between CT images and histopathological results. Patients with stage II cancer were followed up to assess the influence of inaccurate preoperative staging on prognosis. The accuracy of local staging by CT was 47.6% (111/233), with 59.7% (139/233) for tumour stage, and 70.4% (164/233) for nodal stage. The greatest dimension of the tumour on the CT image was about 2 mm less than that measured by histopathology. The estimated volume of tumour was a quarter smaller. The accuracy of predicting malignant lymph nodes by CT was 68.9% (n = 161). Among patients with stage II disease, simultaneous neck dissection was less likely in the understaged group than in the accurately staged one. The reoperation rate was a little higher but not significantly so. We conclude that the accuracy of CT in predicting local staging for tongue cancer was only moderate, because it underestimated the size of the tumour and needed to improve the criteria for detecting malignant lymph nodes. Understaging on CT images may influence the prognosis of patients with early stage tongue cancer.